APOPTOSIS INDUCTION OF CENTELLA ASIATICA ON HUMAN BREAST CANCER CELLS - Babykutty, Suboj; Padikkala, Jose; Sathiadevan, P. P.; Vijayakurup, Vinod; Abdul Azis, T. K.; Srinivas, Priya; Gopala, Srinivas (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
The present study evaluated the ability of methanolic extract of Centella asiatica (Linn) Urban (Umbelliferae) to induce apoptosis in different cancer cell lines. MCF-7 cells emerged as the most sensitive cell line for in vitro growth inhibitory activity. C. asiatica extract induced apoptosis in MCF-7 cells as indicated by nuclear condensation, increased annexin staining, loss of mitochondrial membrane potential and induction of DNA breaks identified by TUNEL reactivity. It is possible that the use of C. asiatica extract as a component in herbal medicines could be justifiable.